Pendampingan Penguatan Branding UMKM Jamu “Mak Diah” Di Desa Ngrimbi Sebagai Bentuk Peningkatan Strategi Ekspansi Pasar - M. Fahrezi Ramadhani; Mu’tassim Billah; Ajie Pandu Suarga; Permata ELG Purba; Daru Teja Sasangka; Satria Ardhana (Manajemen Kreatif Jurnal, 2023)
The strength of branding on a product is something that must be considered by all entrepreneurs, especially UMKM, so that the products marketed have higher competitiveness compared to their competitors. The community service carried out by the East Java UPN Veterans KKNT group of 10 provided assistance in strengthening the branding of one of the MSMEs in Ngrimbi Village, namely Jamu "Mak Diah". Based on the results of observations identified that these MSMEs do not yet have branding that enhances market expansion strategies. The assistance that will be provided will focus on product packaging and logos. After the mentoring was finished, Group 10 monitored and evaluated the effect of strengthening branding on the level of herbal medicine sales after completing it.